Phylogenetic analysis of small ruminant lentiviruses in Germany and Iran suggests their expansion with domestic sheep - Vahid Molaee; Moira Bazzucchi; Gian Mario De Mia; Vahid Otarod; Darab Abdollahi; Sergio Rosati; Gesine Lühken (Scientific Reports, 2020)
Small ruminant lentiviruses (SRLVs) are found in sheep in Germany and Iran. SRLVs have been classified into four genotypes: A–C and E. Genotype A has been subdivided into 20 subtypes. Previous studies suggested that, first, the ancestors of genotype A are those SRLVs found in Turkey, second, the evolution of SRLVs is related to the domestication process, and, third, SRLV infection was first observed in sheep in Iceland and the source of that infection was a flock imported from Germany. This study generated, for the first time, partial SRLV sequence data from German and Iranian sheep, enhancing our knowledge of the genetic and evolutionary relationships of SRLVs, and their associations with the domestication process. Based on 54 SRLV sequences from German and Iranian sheep, our results reveal: (1) SRLV subtypes A4, A5, A11, A16 and A21 (new) are found in German sheep and A22 (new) in Iranian sheep. (2) Genotype A has potentially an additional ancestor (A22), found in Iran, Lebanon and Jordan. (3) Subtype A22 is likely an old version of SRLVs. (4) The transmission routes of some SRLVs are compatible with domestication pathways. (5) This study found no evidence of Icelandic subtype A1 in German sheep.